Vitamin D and immune responses: how much is too much? - Nurul Ratna Mutu Manikam (World Nutrition Journal, 2022)
Vitamin D is a sunshine vitamin that is widely known for bone health. The main source of vitamin D from exposure to ultraviolet B radiation, whereas only 20% from natural and fortified food. Recent studies concluded that vitamin D has a putative role in reducing the risk of viral respiratory infection by suppressing pro-inflammatory cytokines and delaying increasing anti-inflammatory cytokines response. Whereas, vitamin D regulates innate immunity through macrophage and dendrite cell activity as well as an adaptive immune response through lymphocyte T cells response.